Desempeño laboral en el área de despacho de la empresa Altec en la Ciudad de Babahoyo - Seraquives Cepeda, Heydi Melissa (2019)
The present case study shows the labor performance of the workers in Altec's dispatch area. This investigation was carried out through the inductive method which allowed to know in depth the objective of this investigation which is to know the level of performance of the company's collaborators and the type of training they have to carry out their work in a correct manner. The tool that was applied was the interview which was conducted to the staff that makes up the dispatch area with which reliable information was obtained at the time of identifying the problems. Some scenarios were evaluated whose results may be of interest to the directors of this company and could be taken as a basis for corporate studies